2005
DOI: 10.1139/b05-083
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of boreal white spruce (Picea glauca) in pristine conifer-dominated and mixedwood forest stands

Abstract: White spruce ( Picea glauca (Moench) Voss) is a characteristic primary species of the Canadian boreal forest region, where it occurs in conifer-dominated and mixedwood forest types. Genetic diversity and population structure of white spruce may differ between the conifer-dominated and mixedwood forest types owing to the inherent differences in stand structure and dynamics. The objective of our study was to determine genetic diversity and population structure of pristine white spruce stands as they occur in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 23 publications
6
26
0
Order By: Relevance
“…Overall, the genetic distance analysis showed a high level of homogeneity among populations which could be due to the species characteristics. In fact, the relative small genetic distance values reported in the present analysis are consistent with other studies on Picea glauca populations in various provinces that used various molecular markers and allozymes (Rajora et al, 2005;Tremblay and Simon, 1989;Alden and Loopstra, 1987). In general, the genetic similarity among the populations suggests that these populations could have originated from a common source.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, the genetic distance analysis showed a high level of homogeneity among populations which could be due to the species characteristics. In fact, the relative small genetic distance values reported in the present analysis are consistent with other studies on Picea glauca populations in various provinces that used various molecular markers and allozymes (Rajora et al, 2005;Tremblay and Simon, 1989;Alden and Loopstra, 1987). In general, the genetic similarity among the populations suggests that these populations could have originated from a common source.…”
Section: Discussionsupporting
confidence: 91%
“…The fact that Picea glauca populations are fairly distributed should promote the exchange of genes among populations. Hence, it is rare to find alleles that are unique to a given populations, and the frequencies of the main alleles are generally similar from one population to another (Rajora et al, 2005;Tremblay and Simon, 1989;Alden and Loopstra, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The mean number of alleles, observed and expected heterozygosities for SSR loci (A=11-36; H o =0.549-0.718; H e =0.877-0.944; see Electronic supplementary materials, Appendix 1) were also relatively higher than those estimated with the same type and number of markers in conifers with wide geographical distributions, such as Larix occidentalis (A=5.5, H o =0.521, H e =0.580; Khasa et al 2006), Pinus strobus (A=9.6, H o =0.522, H e =0.607; Rajora et al 2000;Marquardt and Epperson 2004), Pinus contorta (A=21.0, H e =0.425; Thomas et al 1999), Picea glauca (A=16.4, H o =0.649, H e =0.851; Rajora et al 2005), and also P. menziesii (A=7.5, H e =0.673; Amarasinghe and Carlson 2002) studied earlier. The difference can be explained by the fact that the SSR loci in our study were preselected as the most polymorphic.…”
Section: Discussionmentioning
confidence: 99%
“…Low F IS values have been reported for other Picea spp., such as P. alcoquiana (0.018; Aizawa et al 2008), P. asperata (0.005; Luo et al 2005), P. breweriana (0.003; Ledig et al 2005), P. mariana (-0.025; Gamache et al 2003;0.02;Perry and Bousquet 2001) and P. rubens (0.021; Rajora et al 2000). In addition, significantly positive F IS values have been reported for P. chihuahuana (0.185; Ledig et al 1997), P. glauca (0.226; Rajora et al 2005) and P. sitchensis in peripheral areas (0.17; . A clear relationship is not shown between the (Table 4) indicate that any population of P. koyamae that was derived from a small number of related individuals in core or peripheral areas might increase the degree of inbreeding.…”
Section: Discussionmentioning
confidence: 99%
“…Although the analysis of BOTTLENECK indicated that these populations have not experienced a recent reduction in effective population size, it does not deny that they experienced bottlenecks in the far past. Some populations of Picea have shown high fixation indices (Ledig et al 1997;Rajora et al 2005) and the existence of selfing (Innes and Ringius 1990;Ledig et al 2000;Flores-Lopéz et al 2005). These results suggest that over several generations, small and isolated populations of P. koyamae have survived with little gene flow, and have sustained themselves while increasing the degree of inbreeding.…”
Section: Discussionmentioning
confidence: 99%